THE USE OF THE DICTATION METHOD TO IMPROVE HIGH SCHOOL STUDENTS ABILITY TO WRITE AND READ HIRAGANA LETTERS - Sanggale, Siprianus; Najoan, Franky R.; Masoko, Marly C.A. (SoCul: International Journal of Research in Social Cultural Issues, 2022)
The purpose of this study is to determine the ability of students in writing and reading Hiragana letters before the use of the dictation method In addition to determine the improvement of students ability to write and read Hiragana letters after the use of the dictation method The ability to capture and accurately receive what is said or dictated by the teacher both in writing and spelling is called the dictation method This study used a pre experimental design with a pre test and post test group model The samples in this study were students of class XI MIPA 1 of SMA Katolik Karitas Tomohon The instrument used was a test In this study it was found that there were differences in the results of processed data namely the pre test score of 33 07 and post test 96 54 and gain 63 47 After that the pre test and post test results were tested using t test and resulted in a t count value of 31 90 Therefore it can be concluded that the ability to write and read Hiragana letters increased after being treated with the dictation method < p>